Patient-reported outcomes after lateral unicompartmental and total knee arthroplasty: a propensity score-matched cohort study - Mustafa Hariri; Reza Sorbi; Babak Moradi; Johannes Weishorn; Raphael Trefzer; Tobias Reiner; Tilman Walker; Timo Albert Nees (Archives of Orthopaedic and Trauma Surgery, 2026)
Abstract Introduction Comparative evidence on patient-reported outcomes (PROs) after lateral unicompartmental knee arthroplasty (UKA) and total knee arthroplasty (TKA) remains limited. We compared PROs between cohorts matched for demographic characteristics and baseline knee function. Materials and methods Prospectively collected single-center data were retrospectively analyzed. Lateral UKA was performed for isolated lateral-compartment osteoarthritis and TKA predominantly for multicompartmental disease. One-to-one propensity score matching incorporated age and body mass index, exact matching on sex, and restrictions on age and preoperative Oxford Knee Score (OKS), yielding 31 pairs. Postoperative OKS was the primary outcome. Secondary outcomes included OKS improvement, Forgotten Joint Score (FJS), University of California, Los Angeles (UCLA) activity score, OKS minimal clinically important difference (MCID) achievement, and FJS patient acceptable symptom state (PASS) attainment. Results All matching covariates achieved acceptable balance (absolute standardized mean differences < 0.20). Postoperative OKS did not differ significantly (UKA, 38.9 ± 7.0; TKA, 39.8 ± 7.5; mean paired difference [TKA minus UKA], 0.94; 95% confidence interval [CI], − 2.57 to 4.44; p = 0.590). No significant differences were detected for OKS improvement (difference, 0.77; 95% CI, − 2.62 to 4.17; p = 0.644) or FJS (difference, 0.83; 95% CI, − 12.53 to 14.19; p = 0.900). UCLA scores were higher after TKA (difference, 0.93; 95% CI, 0.26 to 1.60; p = 0.008). MCID achievement (UKA, 90.3%; TKA, 93.5%; p = 1.000) and PASS attainment (UKA, 67.7%; TKA, 77.4%; p = 0.774) did not differ significantly. Conclusions No significant differences in postoperative OKS, OKS improvement, or FJS were detected, whereas UCLA scores were higher after TKA. Given differing indications and limited sample size, these findings do not establish equivalence or comparative effectiveness between procedures.